1996
DOI: 10.1002/(sici)1099-050x(199621)35:1<87::aid-hrm6>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Downsizing and the hyper-effective manager: The shifting importance of managerial roles during organizational transformation

Abstract: This article describes how managerial roles change in importance during periods of significant organizational transition. An interdisciplinary approach reveals that (1) the competing values framework is a useful framework for examining this question; (2) the transformational roles increase as expected during downsizing; (3) three of four transactional roles also increase during downsizing. This last counterintuitive finding is illuminated by the interdisciplinary model developed. Overall, managers show signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 15 publications
1
12
0
1
Order By: Relevance
“…A riskaverse, conservative strategy often replaces risk-seeking behavior when managers are more concerned with avoiding loss (Tversky & Kahneman, 1991;Wiseman & Bromiley, 1996). It is worth noting that although the wave of mergers and acquisitions in the 1990s led to a shift in emphasis of leadership roles toward transformational and transactional roles (Belasen, Benke, DiPadova, & Fortunato, 1996;Belasen, 2000), the conditions that existed during the recent financial crash in 2007-08, were qualitatively different. Although downsizing forced companies to eliminate redundancies and increase productivity through layoffs, surviving managers needed to reorient their mind-sets and adopt new ways of thinking and doing.…”
Section: Research Objectivessupporting
confidence: 56%
See 3 more Smart Citations
“…A riskaverse, conservative strategy often replaces risk-seeking behavior when managers are more concerned with avoiding loss (Tversky & Kahneman, 1991;Wiseman & Bromiley, 1996). It is worth noting that although the wave of mergers and acquisitions in the 1990s led to a shift in emphasis of leadership roles toward transformational and transactional roles (Belasen, Benke, DiPadova, & Fortunato, 1996;Belasen, 2000), the conditions that existed during the recent financial crash in 2007-08, were qualitatively different. Although downsizing forced companies to eliminate redundancies and increase productivity through layoffs, surviving managers needed to reorient their mind-sets and adopt new ways of thinking and doing.…”
Section: Research Objectivessupporting
confidence: 56%
“…Hypereffectivity is associated with unsustainable efforts to perform activities and roles relentlessly and continuously. Everything is important and nothing can be taken for granted (Belasen, Benke, DiPadova, & Fortunato, 1996). The significant increase in seven (the monitor role turned out to be bimodal) of the eight CVF roles, including the critical producer and director roles, suggested that the sample of managers studied may have become not only more effective but also what the researchers labeled as hyper-effective.…”
Section: Research Objectivesmentioning
confidence: 68%
See 2 more Smart Citations
“…Es decir, sabiendo el tipo de cultura dominante en alguna organización, se puede determinar el perfil de líder necesario, ya sea sus cualidades, atributos y comportamientos que debe tener para lograr efectividad en sus seguidores. Estos atributos o comportamientos de los líderes para cada una de las culturas muestran que las culturas del hemisferio superior del modelo, clan y adhocracia, tienen atributos propios de un líder transformacional, mientras que el hemisferio inferior, cultura mercado y jerárquica, tienen características de un líder transaccional (Belasen et al, 1996).…”
Section: Liderazgo Transaccionalunclassified